PENGARUH KONSENTRASI DAN LAMA PERENDAMAN DALAM SUPERNATAN KULTUR Bacillus sp.2 DUCC-BR-KI.3 TERHADAP PERTUMBUHAN STEK HORISONTAL BATANG JARAK PAGAR (Jatropha curcas L.) - Pamungkas, Febriani Tri; Damranti, Sri; Raharjo, Budi (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT--Jarak pagar (J. curcas L.) is a plant whose the seed can produce oil or it is known as biodiesel. J.  curcas's oil is the source of alternative oil energti that can be renewable and environmentally safe. Another ways  to increase the production of J. curcas's oil is by improving its  productivity. This activity cannot be separated from the problem of supplying the seed. Stem cutting  is one of the most ways to provide the seed than another way. The growth of stem cutting can be stimulated by giving ZPT that is IAA both naturally and synthetically. Bacillus  sp.2  DUCC-BR-KL.3 supernatant culture that contain IAA can be one of naturally alternative hormone. The aims of this research was to study the effect of concentration and submersion period in Bacillus  sp.2 DUCC-BR-KL.3  supernatant culture to the growth of J. curcas L. hoizontal stem cutting. This experiment was  condueted in Plant's Biologi Structure and Function Laboratory, MIPA faculty, Diponegoro University. Experimental design used in this research is Completely Random  Design with Factorial pattern 5x4 by using 5 replications. The first factor was concentration, ie P0 (control), P1 (25%), P2 (50%), P3 (75%) and P4 (100%). The  second factor was submerged periods, i.e T1 (1 hour), T2 (2 hours), and T3 (3 hours). The data were analyzed by using Kruskal-Wallis Test and ANOVA, if there are significantly  influence, were analyzed by using Duncan multiple range test with 95% confidence intevals that is in the variable of root lenght and weight of dry root. The result of this sudy showed that the giving of Bacillus sp.2 DUCC-BR-KL.3 supernatant culture influence to improve the bud and root growth of J. curcas L. Keywords :  Jatropha culcos L., supernalant, concentration, growth